32x(X+3)=8
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(\left(2x-3\right)\left(3x^2+1\right)-6x\left(x^2-x+1\right)+3x^2-2x=10\)
\(\Leftrightarrow6x^3+2x-9x^2-3-6x^3+6x^2-6x+3x^2-2x=10\)
\(\Leftrightarrow-6x-3=10\)
=>-6x=13
hay x=-13/6
b: \(\Leftrightarrow3x^2-3x+x-2-3x^2+5x=-8-5x\)
=>3x-2=-5x-8
=>8x=-6
hay x=-3/4
c: \(\Leftrightarrow64x^3-27-64x^3+32x^2-32x^2+x=20\)
=>x-27=20
hay x=47
a)3(x-1)(2x-1)-5(x+8)(x-1)=0
<=>(x-1)(6x-3-5x-40)=0
<=>(x-1)(x-43)=0
b)2x^3+3x^2-32x-48=0
<=>x^2(2x+3)-16(2x+3)=0
<=>(2x+3)(x-4)(x+4)=0
học tốt
1, (x-1)(x+2)(x+3)(x-6)+32x^2
= (x^2 - 7x + 6)(x^2 + 5x + 6) + 32x^2
đặt x^2 - x + 6 = a ta có
(a - 6x)(a + 6x) + 32x^2
= a^2 - 36x^2 + 32x^2
= a^2 - 4x^2
= (a - 2x)(a + 2x)
= (x^2 - x + 6 - 2x)(x^2 - x + 6 + 2x)
= (x^2 - 3x + 6)(x^2 + x + 6)
2, (x+1)(x-4)(x+2)(x-8)+4x^2
= (x^2 + 7x - 8)(x^2 - 2x - 8) + 4x^2
đặt x^2 + 2,5x - 8 = a ta có
(a + 4,5x)(a - 4,5x) + 4x^2
= a^2 - 81/4x^2 + 4x^2
= a^2 - 65/4x^2
\(=\left(a-\sqrt{\frac{65}{4}}x\right)\left(a+\sqrt{\frac{65}{4}}x\right)=\left(x^2+\frac{5}{2}x-8+\sqrt{\frac{65}{4}}x\right)\left(x^2+\frac{5}{2}x-8-\sqrt{\frac{65}{4}x}\right)\)
`@` `\text {Ans}`
`\downarrow`
`32 \times (x + 3) = 8`
`=> x + 3 = 8 \div 32`
`=> x + 3 = 1/4`
`=> x = 1/4 - 3`
`=> x = -11/4`
Vậy, `x = -11/4.`
X+3=32:8
X+3=4
X =4-3
X =1